Position-based ANN impedance control for a three-fingered robot hand / R. L. A. Shauri, M. A. A. M. Sabri and A. B. Roslan - Shauri, R. L. A.; Sabri, M. A. A. M.; Roslan, A. B. (UiTM Press, 2024)
A feedforward ANN was previously developed for recognition of two objects i.e. a spongy ball and a plastic bottle but was verified through simulation only. In this work, the feasibility of the ANN model is tested by applying it to the robot’s impedance control which takes the exerted force at the finger as input while resulting in an output for the selection rule of the impedance stiffness parameter,